(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In patients with social and anamnestic risk factors for the development of cervicitis, the vaginal microbiome should be assessed and a test performed for the presence of a possible causative agent of inflammation.